Not in My Community: Social Pressure and the Geography of Dismissals - Bassanini, Andrea; Brunello, Giorgio; Caroli, Eve (Journal of Labor Economics, 2017)
We investigate the impact of local social pressure on firms’ firing decisions. Using linked employer-employee data, we show that secondary establishments located further away from headquarters have higher dismissal rates than those located closer. The effect of distance on dismissals is stronger, the greater the visibility of the firm in the local community of its headquarters and the larger the degree of selfishness of that community. We show that these findings can be explained by the social pressure exerted by the communities where firms’ headquarters are located, which induces CEOs to refrain from dismissing at short distance from their headquarters.